2017
DOI: 10.1139/cjfas-2017-0114
|View full text |Cite
|
Sign up to set email alerts
|

At the forefront: evidence of the applicability of using environmental DNA to quantify the abundance of fish populations in natural lentic waters with additional sampling considerations

Abstract: Environmental DNA (eDNA) sampling has proven to be a valuable tool for detecting species in aquatic ecosystems. Within this rapidly evolving field, a promising application is the ability to obtain quantitative estimates of relative species abundance based on eDNA concentration rather than traditionally labor-intensive methods. We investigated the relationship between eDNA concentration and Arctic char (Salvelinus alpinus) abundance in five well-studied natural lakes; additionally, we examined the effects of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 19 publications
6
60
1
Order By: Relevance
“…Many studies to date have sought to compare the reliability of eDNA to conventional sampling methods in estimating both occupancy and abundance of target organisms. In general, eDNA has performed well for representing occupancy of species (Dougherty et al., ; Pilliod et al., ; Smart et al., ), and some studies have found strong agreement between abundance or biomass of organisms and abundance of eDNA in the environment (Doi et al., ; Klobucar et al., ). Specific to crayfishes, studies have generally found eDNA to accurately represent occupancy of crayfishes, potentially with more sensitivity than some conventional methods, but eDNA has performed poorly in reflecting crayfish abundance (Agersnap et al., ; Cai et al., ; Dougherty et al., ; Larson et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies to date have sought to compare the reliability of eDNA to conventional sampling methods in estimating both occupancy and abundance of target organisms. In general, eDNA has performed well for representing occupancy of species (Dougherty et al., ; Pilliod et al., ; Smart et al., ), and some studies have found strong agreement between abundance or biomass of organisms and abundance of eDNA in the environment (Doi et al., ; Klobucar et al., ). Specific to crayfishes, studies have generally found eDNA to accurately represent occupancy of crayfishes, potentially with more sensitivity than some conventional methods, but eDNA has performed poorly in reflecting crayfish abundance (Agersnap et al., ; Cai et al., ; Dougherty et al., ; Larson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its somewhat recent emergence for macrobiota in freshwater species surveys, eDNA has been successfully applied to a variety of freshwater taxa including amphibians (Goldberg, Pilliod, Arkle, & Waits, ; Pilliod, Goldberg, Arkle, Waits, & Richardson, ), crayfishes (Cai et al., ; Tréguier et al., ), fishes (Minamoto, Yamanaka, Takahara, Honjo, & Kawabata, ; Takahara, Minamoto, & Doi, ), gastropods (Goldberg, Sepulveda, Ray, Baumgardt, & Waits, ), insects (Thomsen et al., ), molluscs (Egan et al., ) and reptiles (Piaggio et al., ). Further, eDNA has shown promising results in both lentic (Klobucar, Rodgers, & Budy, ; Takahara et al., ) and lotic (Doi et al., ; Katano, Harada, Doi, Souma, & Minamoto, ) environments, although its reliability in lotic environments may be challenged by the downstream transport of detectable eDNA.…”
Section: Introductionmentioning
confidence: 99%
“…As an efficient alternative, the analysis of environmental DNA (eDNA), DNA shed or expelled from organisms into the environment, has been used to assess species diversity, primarily in aquatic environments (Andruszkiewicz, Starks, et al, ; Boussarie et al, ; DiBattista et al, ; Everett & Park, ; Jerde, Mahon, Chadderton, & Lodge, ; Klymus, Marshall, & Stepien, ; Li et al, ; Parsons, Everett, Dahlheim, & Park, ; Port et al, ; Stat et al, ; Thomsen, Kielgast, Iversen, Moller, et al, ; Thomsen, Kielgast, Iversen, Wiuf, et al, ; Ushio et al, ). Despite the growing use of eDNA to catalog the presence and absence of species, the quantitative description of the relative abundance of species (or guilds of functionally similar species) with eDNA remains an open question (Bakker et al, ; Elbrecht & Leese, ; Evans et al, ; Hänfling et al, ; Kelly, Port, Yamahara, & Crowder, ; Kelly, Port, Yamahara, Martone, et al, ; Klobucar, Rodgers, & Budy, ; Lacoursière‐Roussel, Côté, Leclerc, & Bernatchez, ; Piñol, Senar, & Symondson, ; Port et al, ; Sigsgaard et al, ; Stoeckle, Soboleva, & Charlop‐Powers, ; Taberlet, Bonin, Zinger, & Coissac, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, degree of correlation between eDNA concentration and abundance demonstrated in the field is variable between studies. A recent study of a stream‐dwelling char demonstrated a high correlation (Wilcox et al, ), but other studies reported marginally significant correlations or secondary contribution of abundance to eDNA amount (Doi et al, ; Erickson et al, ; Lacoursière‐Roussel, Côté, Leclerc, & Bernatchez, ; Klobucar, Rodgers, & Budy, ; Nevers et al, ; Pilliod, Goldberg, Arkle, Waits, & Richardson, ; Thomsen et al, ; Yamamoto et al, ). In some studies, eDNA concentration did not correlate with the biomass of the target animals (Biggs et al, ; Spear, Groves, Williams, & Waits, ).…”
Section: Introductionmentioning
confidence: 99%